Hubungan BBLR dan Pemberian ASI Ekslusif dengan Kejadian Stunting - Wulandari, Devi Kartika; Fitri, Destiana; Silaban, Desy Ratna Sari; Yunita, Desri; Mayasari, Devi; Nababan, Tiarnida (Universitas Malahayati, 2024)
ABSTRACT Stunting is a major threat to the quality of Indonesian people, as well as a threat to the nation's competitiveness. This is because being stunted, not only disrupts physical growth (short stature/stunt), but also disrupts brain development. The aim of this research is to determine the relationship between LBW and exclusive breastfeeding with the incidence of stunting. The type of research used is a descriptive analytical survey with a cross sectional design. The population in this study was all mothers with toddlers who were weighed at the Johan Pahlawan Health Center, Meulaboh City, West Aceh Regency, totaling 50 people. The subject sampling technique used a total sampling of 50 people. The type of data used in this research is primary data. The instruments used in this research were observation sheets and questionnaires to measure birth weight and the incidence of stunting. The variable for exclusive breastfeeding was collected using a questionnaire. Research data analysis was univariate and bivariate analysis using the chi square test. The results of the study explained that there was a relationship between LBW and the incidence of stunting (P = 0.004) and there was a relationship between exclusive breastfeeding and the incidence of stunting (P = 0.008). Based on the incidence of LBW, the majority of respondents were in the not LBW category as many as 32 people (63%) and minority respondents were in the LBW category as many as 18 people (36%). Keywords: LBW, Exclusive Breastfeeding, Stunting ABSTRAK Stunting merupakan ancaman besar terhadap kualitas masyarakat Indonesia, sekaligus ancaman terhadap daya saing bangsa. Sebab, stunting tidak hanya mengganggu pertumbuhan fisik (perawakan pendek/stunt), namun juga mengganggu perkembangan otak. Tujuan penelitian ini adalah untuk mengetahui hubungan BBLR dan pemberian ASI eksklusif dengan kejadian stunting. Jenis penelitian yang digunakan adalah survei deskriptif analitis dengan desain cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki balita yang ditimbang di Puskesmas Johan Pahlawan Kota Meulaboh Kabupaten Aceh Barat yang berjumlah 50 orang. Teknik pengambilan sampel subjek menggunakan total sampling sebanyak 50 orang. Jenis data yang digunakan dalam penelitian ini adalah data primer. Instrumen yang digunakan dalam penelitian ini adalah lembar observasi dan kuesioner untuk mengukur berat badan lahir dan kejadian stunting. Variabel pemberian ASI eksklusif dikumpulkan dengan menggunakan kuesioner. Analisis data penelitian adalah analisis univariat dan bivariat dengan menggunakan uji chi square. Hasil penelitian menjelaskan ada hubungan BBLR dengan kejadian stunting (P=0,004) dan ada hubungan ASI Eksklusif dengan kejadian stunting (P=0,008). Berdasarkan kejadian BBLR, mayoritas responden berada pada kategori tidak BBLR sebanyak 32 orang (63%) dan minoritas responden berada pada kategori BBLR sebanyak 18 orang (36%). Kata Kunci: BBLR, Pemberian ASI Eksklusif, Pengerdilan